Gabapentin as an adjuvant for postoperative pain management in dogs undergoing mastectomy - CROCIOLLI, Giulianne Carla (J Vet Med Sci, 2015)
This study aimed to evaluate the analgesic efficacy of gabapentin as an adjuvant for postoperative pain management in dogs. Twenty dogs undergoing mastectomy were randomized to receive perioperative oral placebo or gabapentin (10 mg/kg). All dogs were premedicated with intramuscular acepromazine (0.03 mg/kg) and morphine (0.3 mg/ kg). Anesthesia was induced with propofol (4 mg/kg) intravenously and maintained with isoflurane. Intravenous meloxicam (0.2 mg/kg) was administered preoperatively. Postoperative analgesia was evaluated for 72 hr. Rescue analgesia was provided with intramuscular morphine (0.5 mg/kg). Dogs in the Placebo group received significantly more morphine doses than the Gabapentin group (P=0.021), despite no significant differences in pain scores. Perioperative gabapentin reduced the postoperative morphine requirements in dogs after mastectomy.